Proposta e aplicação de um método para avaliação do grau de maturidade no escritório de projetos da unidade operacional de uma empresa multinacional do setor elétrico - Silva, Francisco Iranildo da (2019)
With a globalization competition between companies has increased. Thus, as organizations that seek methods and alternatives to leverage the performance of indicators and processes, improve the management and implementation of PMO projects, or apply methodologies to define the degree of maturity that helped to achieve strategic results. Therefore, the purpose of this work was to propose and implement an evaluation method to define the level of maturity of a department's project, and propose actions / improve the level of performance desired. The average of questions is presented as Applied, with a Quantitative and Qualitative approach and with a purpose of descriptive study. In the working software, the following technical processes were used: bibliographical, documentary, field research and case study. In the case study, the discipline is revealed, aiming to discover the current maturity level and define the desired, and through the results, propose actions for improvement to the degree of maturity of the PMO. A field survey was performed using the standard model of the PMO maturity cube escape in one of the evaluation method steps. The results were discussed and analyzed, and a company opted to perform the improvement plan actions to achieve the maturity level of the project office.